ANALISIS PENGARUH KOMPETENSI, LINGKUNGAN KERJA NON FISIK DAN REWARDS TERHADAP KINERJA KERJA KARYAWAN - Eni Cahyani; Dian Septianti (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT Employee work performance is the result of work achieved by an employee in carrying out tasks in accordance with their responsibilities. There are many factors that affect employee work performance, but in this study only a few factors were discussed including competency, non-physical work environment and rewards. Competence is the ability possessed by someone to carry out the work given to him well. While the non-physical work environment is considered important because it has a direct influence on employees in carrying out and completing work. Other factors, namely rewards, are expected to be able to create healthy competition between employees in order to improve employee work performance. The design used in this study is qualitative descriptive research. Keywords: Competence, Non Physical Working Environment, Rewards, Employee Work Performance